2009
DOI: 10.1007/s11430-009-0184-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of remaining oil viscosity in water- and polymer-flooding reservoirs in Daqing Oilfield

Abstract: The experimental analysis of 21 crude oil samples shows a good correlation between high molecular-weight hydrocarbon components (C 40 + ) and viscosity. Forty-four remaining oil samples extracted from oil sands of oilfield development coring wells were analyzed by high-temperature gas chromatography (HTGC), for the relative abundance of C 21 − , C 21 -C 40 and C 40 + hydrocarbons. The relationship between viscosity of crude oil and C 40 + (%) hydrocarbons abundance is used to expect the viscosity of remaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…With the growing demand for the crude oil and the further exploitation of oilfields, the exploitation of low‐permeability oilfields has attracted more and more attention. Enhancing oil recovery (EOR) is a crucial part in low‐permeability oilfields production 1,2 . Currently, polymer flooding has become one of the most mature and effective EOR methods in oilfields 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…With the growing demand for the crude oil and the further exploitation of oilfields, the exploitation of low‐permeability oilfields has attracted more and more attention. Enhancing oil recovery (EOR) is a crucial part in low‐permeability oilfields production 1,2 . Currently, polymer flooding has become one of the most mature and effective EOR methods in oilfields 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Pang [14] found that, when the injection-production ratio was relatively low in the water/polymer co-flooding, it would have a certain impact on water injection wells, and we should reduce the impact in the development process. Xu et al [15] found that there must be interference between water molecules and polymer molecules in the water/polymer co-flooding. In the process of development, it was necessary to reduce the influence degree in time.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing demand for crude oil, it is well-known that enhanced oil recovery is the top priority of oilfield production. [1][2][3][4] When oilfields enter the late stage of development, the water cut is getting higher and higher. [5][6][7] Afterwards, polymer flooding, the most widely applied method of enhanced oil recovery in oilfields, begins to play its role.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing demand for crude oil, it is well‐known that enhanced oil recovery is the top priority of oilfield production . When oilfields enter the late stage of development, the water cut is getting higher and higher .…”
Section: Introductionmentioning
confidence: 99%